Abstract ID: 198 Monte Carlo simulation and simple model of dose distribution in synchrotron radiation rotational radiotherapy of breast cancer: An experimental phantom study. (October 2017) - Di Lillo, F.; Stevenson, A.W.; Mettivier, G.; Sarno, A.; Castriconi, R.; Hall, C.J.; Häusermann, D.; Russo, P.
Abstract : External beam rotational radiotherapy of breast cancer with kilovoltage photons (kV-EBRT), with the patient in prone position, has been proposed[1] as a possible alternative to conventional radiotherapy with two tangential 6-MV X-ray beams produced by a medical linac with a supine patient. kV-EBRT uses a dedicated setup initially developed for breast CT, with a 320-kVp beam from an orthovoltage X-ray tube rotating in full circles around the breast; CT for tumour localization can be performed by using the same setup. Though dose build-up is not present, rotational summation of dose delivery allows a skin sparing comparable to conventional radiotherapy. We proposed the use of a monoenergetic synchrotron radiation (SR) collimated beam for image-guided rotational radiotherapy for the pendant breast (SR 3 T)[2] . The high flux of SR permits dose rates even greater to that of conventional radiotherapy, while the optimal photon energy can be selected for the treatment. In this work, we present Monte Carlo simulation and a simple model for evaluation of the 3D dose distribution in SR 3 T. The MC code was based on GEANT4 toolkit ver.10.00. We validated these simulations via measurements on breast phantoms performed at the Imaging and Medical Beamline of the Australian Synchrotron. We measured the dose distribution in cylindrical PMMA and polyethylene phantoms at 60 keV, using an ionization chamber, thermoluminescent dosimeters and radiochromic films. This study indicated that for a tumour localized at the centre of a mid-sized breast (14-cm diameter at chest wall), a "skin-to-tumour" dose ratio of 14% can be reached at 60 keV with a collimated SR beam. Non uniform dose distribution to the target (dose painting) can be performed with multiple rotations around the organ. Kilovoltage SR 3 T with suitable radiosensitizers may exploit the dose enhancement factor due to increased photoelectric absorption, at SR beam energies in the 60–110 keV range.